'But I've never sent them any personal details apart from my driver's licence number …': Exploring seniors' attitudes towards identity crime. Issue 1 (January 2017) - Cross, Cassandra
Abstract Identity crime is argued to be one of the most significant crime problems of today. This article examines identity crime, through the attitudes and practices of a group of seniors in Queensland, Australia. It examines their own actions towards the protection of their personal data in response to a fraudulent email request. Applying the concept of a prudential citizen (as one who is responsible for self-regulating their behaviour to maintain the integrity of one's identity) it will be argued that seniors often expose identity information through their actions. However, this is demonstrated to be the result of flawed assumptions and misguided beliefs over the perceived risk and likelihood of identity crime, rather than a deliberate act. This article concludes that to protect seniors from identity crime, greater awareness of appropriate risk-management strategies towards disclosure of their personal details is required to reduce their inadvertent exposure to identity crime.